Illustration:

Evaluate Lim x→0 sin^-1 x-tan^-1x/x^3

$\mathrm{Lim}\frac{{\mathrm{sin}}^{-1}\mathrm{x}-{\mathrm{tan}}^{-1}\mathrm{x}}{{\mathrm{x}}^{3}}\phantom{\rule{0ex}{0ex}}\mathrm{x}\to 0\phantom{\rule{0ex}{0ex}}\mathrm{sin}1\mathrm{x}=\mathrm{x}+\frac{{\mathrm{x}}^{3}}{5}\phantom{\rule{0ex}{0ex}}\mathrm{tan}1\mathrm{x}=\mathrm{x}-\frac{{\mathrm{x}}^{3}}{3}+\frac{{\mathrm{x}}^{5}}{5}+\mathrm{\_\_\_}\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}\mathrm{lim}\phantom{\rule{0ex}{0ex}}\mathrm{x}\to 0=\frac{\mathrm{x}+{\displaystyle \frac{{\mathrm{x}}^{3}}{6}}-\mathrm{x}+{\displaystyle \frac{{\mathrm{x}}^{3}}{3}}}{{\mathrm{x}}^{3}}\phantom{\rule{0ex}{0ex}}\mathbf{}\mathbf{=}\mathbf{}\frac{\mathbf{1}}{\mathbf{6}}\mathbf{+}\frac{\mathbf{1}}{\mathbf{3}}\mathbf{=}\mathbf{}\frac{\mathbf{1}\mathbf{+}\mathbf{2}}{\mathbf{6}}\mathbf{=}\frac{\mathbf{1}}{\mathbf{2}}$